2008
DOI: 10.1093/gerona/63.8.841
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Limitation in Self-Described Well-Functioning Older Adults: Importance of Endurance Walk Testing

Abstract: A sizable proportion of elders who report no walking difficulty have observable deficits in walking performance that precede and predict their recognition of mobility limitation. Endurance walk testing can help identify these deficits and provide the basis for treatment to delay progression of mobility loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 32 publications
5
109
1
Order By: Relevance
“…Walking speed over 400 m has been shown to be significantly faster than that for the 6-MWT. 82 Test-retest reliability has been established 83 and significant associations have been reported between 400-m walk time and aerobic capacity, lower extremity strength and power, 40,84 mobility limitation 85 as well as mortality prognosis in older persons. [86][87][88][89] Minimally significant change for the 400-m walk test has been estimated at 20-30 s, while 50-60 s was suggested as criteria for substantial change.…”
Section: Adt: Body Composition and Physical Functionmentioning
confidence: 99%
“…Walking speed over 400 m has been shown to be significantly faster than that for the 6-MWT. 82 Test-retest reliability has been established 83 and significant associations have been reported between 400-m walk time and aerobic capacity, lower extremity strength and power, 40,84 mobility limitation 85 as well as mortality prognosis in older persons. [86][87][88][89] Minimally significant change for the 400-m walk test has been estimated at 20-30 s, while 50-60 s was suggested as criteria for substantial change.…”
Section: Adt: Body Composition and Physical Functionmentioning
confidence: 99%
“…Previous studies of self-reported mobility disability in older adults have focused on predictors of incident mobility disability rather than on outcomes. [4][5][6][7] In order to be successfully integrated into clinical practice and health policy, a marker of mobility disability must be easily accessible, such as self-report, and should predict subsequent health outcomes and health care utilization in a broad range of older adults. Therefore, our study examines a nationally representative sample of Medicare beneficiaries aged 65 years or older to determine the association between mobility disability, defined as self-reported limitations in walking 1/4 mile, and subsequent mortality, incident basic and instrumental ADL disability, and health care utilization and costs.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, only 25 % of older adults walk outdoors on a regular basis. 10 While a host of studies have focused on the role of individual factors for encouraging or preventing outdoor mobility (e.g., functional status, self-efficacy, outcome expectations), [11][12][13][14] considerably less research has examined the importance of the urban built environment for older adults aging in place. Urban environmental barriers subjectively reported by older adults include poor access to public transportation, discontinuous or uneven sidewalks, curbs, and inadequate lighting.…”
Section: Introductionmentioning
confidence: 99%